Rekomendasi Klasifikasi Nasabah BSI Mengikuti Program Pesta Hadiah dan Labbaik Special Gift Menggunakan Algoritma C4.5 - Resty Annisa; Aidil Afriansyah (JUKI : Jurnal Komputer dan Informatika, 2022)
PT. Bank Syariah Indonesia KCP Bintaro Kebayoran Arcade 1 is one of the banks that provides gift party program services and special gift lab programs for customers by opening an account book and making deposits with a certain amount and later will be exchanged for prizes in kind to customers. On PT. Bank Syariah Indonesia KCP Bintaro Kebayoran Arcade 1 offers both programs to customers there is a problem because both programs require deposits with a certain nominal amount. Meanwhile, the customers who arrive have different nominal account balances, work backgrounds, and incomes. By applying data mining and using the C4.5 algorithm, Bank Syariah Indonesia customer data can be predicted with fairly high accuracy using training data and testing data of 94.65% and 88.18% with two different split data cases.